DETEKSI BAKTERI Staphylococcus sp PADA SWAB HANDPHONE DENGAN TINGKAT PERSONAL HYGIENE MAHASISWA IIK BHAKTI WIYATA KEDIRI - Febriana Faldita; Veronica Puspitasari; Triffit Imasari (LPPM Universitas Abdurrab, 2022)
Mobile phones as a learning tool among students are used during the temporary closure of educational institutions as an effort to prevent the spread of the COVID-19 pandemic around the world. This requires students to do Study From Home learning, a learning process that is carried out virtually using communication media such as cellphones, laptops, and tablets. This causes the intensity of using cellphones to become more frequent every time and generally ignores hygiene. Overall the level of bacterial contamination of cell phones is 70% with the pathogenic bacteria Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas sp., Staphylococcus saprophyticus, Enterobacter aergene, Escherichia coli, Citrobacter intermedites, and Citrobacter freundii. The purpose of the research was to identify Staphylococcus sp and to know the correlation of Staphylococcus sp. with the personal hygiene level of IIK Bhakti Wiyata Kediri students. The research method is correlation analytic using purposive sampling technique with 16 cell phone swab samples. This research used the culture test on BAP, MSA, NAS and Gram staining as well as a questionnaire to determine the level of personal hygiene. The results of the research identified Staphylococcus aureus by 75% and Staphylococcus epidermidis by 25% and the results of the questionnaire on the level of personal hygiene with a sufficient category of 75%. The conclusion of the research is that there is Staphylococcus sp in cellphone swabs and there is a correlation of the presence of Staphylococcus sp bacteria with the level of personal hygiene in IIK Bhakti Wiyata students.